Salesforce Platform App Builder Certification Guide A beginner's guide to building apps on the Salesforce Platform and passing the Salesforce Platform App Builder exam - Goodey, Paul; Goodey, Paul (Packt Publishing, 2020)
Get up to speed with the essential concepts and techniques necessary to prepare for the Salesforce Platform App Builder certification examKey FeaturesPrepare for the Salesforce Platform App Builder certification exam by exploring important concepts and expert tips and techniquesDesign the data model, user interface, business logic, and security for custom appsUnderstand the key milestones and considerations when managing an application lifecycleBook DescriptionDo you want to be able to confidently design and build apps that support business processes within the Lightning Platform? Salesforce Platform App Builder Certification Guide not only helps you to do this, but also prepares you for the certification exam.The book starts by describing the core capabilities of the Lightning Platform. You'll learn techniques for data modeling to design, build, and deploy apps without writing code and achieve rapid results with the declarative capabilities that the Lightning Platform provides. Next, you'll explore utilities for importing and exporting data and the features available in the Lightning Platform to restrict and extend access to objects, fields, and records. You'll also be able to customize the Salesforce Lightning Experience user interface (UI) and build functionality for custom buttons, links, and actions. Later, this certification study guide will take you through reporting and the social and mobile features of the Lightning Platform. Finally, you'll get to grips with Salesforce build environments and deployment options.By the end of this Salesforce book, you'll not only have learned how to build data models, enforce data security, and implement business logic and process automation, but also have gained the confidence to pass the Platform App Builder exam and achieve Salesforce certification.What you will learnExplore the core features of the Lightning PlatformDesign and build an appropriate data model for a given scenarioIdentify the Lightning Platform's features and capabilitiesCustomize the Salesforce Lightning Experience UIImplement business logic and process automationIdentify the capabilities of declarative customizationWho this book is forThis book is for beginners and aspiring developers who want to learn how to build apps on the Salesforce Platform or pass the Salesforce Platform App Builder certification exam. Salesforce administrators and existing Salesforce Lightning Platform developers looking to learn more about the declarative, non-programmatic app building capabilities of the Salesforce Lightning Platform will also find this book useful.